Quantifying Improvements in Derived Storm Events from Version 07 of GPM IMERG Early, Late, and Final Data Products over North Carolina - Elizabeth Bartuska; R. Edward Beighley; Kelsey J. Pieper; C. Nathan Jones (Remote Sensing)
In North Carolina (NC), roughly 1 in 4 residents rely on private wells for drinking water. Given the potential for flooding to impact well water quality, which poses serious health hazards to well users, accurate near real-time precipitation estimates are vital for guiding outreach and mitigation efforts. GPM IMERG precipitation data provides a solution for this need. Previous studies have shown that IMERG version 06 performs well throughout NC for capturing event totals. This study investigates changes in precipitation performance from IMERG version 06 to version 07 in NC and surrounding regions. There was significant improvement pertaining to errors quantifying the magnitude of precipitation events; the mean error in event precipitation decreased 75–85%, bias decreased 65–80%, and the root mean square error decreased 15–30% for Early, Late, and Final products as compared to event totals from in situ precipitation gauges. V07 shows improved performance during events in colder conditions, in mountainous regions, and with higher, prolonged intensities. During Hurricane Florence (September 2018), v07 improved precipitation estimates in regions with higher rainfall totals. These findings demonstrate the potential of the IMERG v07 Early and Late data products for the creation of accurate and timely flood models in emergency response applications.